Components of the Gut Microbiome That Influence Bone Tissue‐Level Strength. (4th June 2021) - Luna, Marysol; Guss, Jason D; Vasquez‐Bolanos, Laura S; Castaneda, Macy; Rojas, Manuela Vargas; Strong, Jasmin M; Alabi, Denise A; Dornevil, Sophie D; Nixon, Jacob C; Taylor, Erik A; Donnelly, Eve; Fu, Xueyan; et al.
ABSTRACT: Modifications to the constituents of the gut microbiome influence bone density and tissue‐level strength, but the specific microbial components that influence tissue‐level strength in bone are not known. Here, we selectively modify constituents of the gut microbiota using narrow‐spectrum antibiotics to identify components of the microbiome associated with changes in bone mechanical and material properties. Male C57BL/6J mice (4 weeks) were divided into seven groups ( n = 7–10/group) and had taxa within the gut microbiome removed through dosing with: (i) ampicillin; (ii) neomycin; (iii) vancomycin; (iv) metronidazole; (v) a cocktail of all four antibiotics together (with zero‐calorie sweetener to ensure intake); (vi) zero‐calorie sweetener only; or (vii) no additive (untreated) for 12 weeks. Individual antibiotics remove only some taxa from the gut, while the cocktail of all four removes almost all microbes. After accounting for differences in geometry, whole bone strength was reduced in animals with gut microbiome modified by neomycin (−28%, p = 0.002) and was increased in the group in which the gut microbiome was altered by sweetener alone (+39%, p < 0.001). Analysis of the fecal microbiota detected seven lower‐ranked taxa differentially abundant in animals with impaired tissue‐level strength and 14 differentially abundant taxa associated with increased tissue‐level strength. Histological and serum markers of bone turnover and trabecular bone volume per tissue volume (BV/TV) did not differ among groups. These findings demonstrate that modifications to the taxonomic components of the gut microbiome have the potential to decrease or increase tissue‐level strength of bone independent of bone quantity and without noticeable changes in bone turnover. © 2021 American Society for Bone and Mineral Research (ASBMR).